Inmigración, servicios públicos e integración social - Mora Castro, Albert (Cuadernos de Trabajo Social, 2007)
The configuration of our societies as multicultural places has caused the integration of diversity to become one of the major challenges that we face currently. Social inclusion of immigrants in the receiving societies faces obstacles due to the difficulties that exist in the recognition of their social rights. With this article we seek to understand the conditions produced by immigrants’ access to public resources, in particular, the Health System.